2009
DOI: 10.1111/j.1742-4658.2009.07401.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral entry mechanisms: the increasing diversity of paramyxovirus entry

Abstract: The paramyxovirus family contains established human pathogens such as the measles virus and human respiratory syncytial virus, as well as emerging pathogens including the Hendra and Nipah viruses and the recently identified human metapneumovirus. Two major envelope glycoproteins, the attachment protein and the fusion protein, promote the processes of viral attachment and virus‐cell membrane fusion required for entry. Although common mechanisms of fusion protein proteolytic activation and the mechanism of membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
134
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 102 publications
(144 reference statements)
1
134
0
2
Order By: Relevance
“…However, receptor binding and fusion are mediated by two different glycoproteins, the attachment and fusion (F) proteins, respectively, requiring a mechanism by which the two processes can be linked. This is accomplished by a virus-specific interaction between the two proteins (9,10,13,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, receptor binding and fusion are mediated by two different glycoproteins, the attachment and fusion (F) proteins, respectively, requiring a mechanism by which the two processes can be linked. This is accomplished by a virus-specific interaction between the two proteins (9,10,13,19).…”
mentioning
confidence: 99%
“…However, receptor binding and fusion are mediated by two different glycoproteins, the attachment and fusion (F) proteins, respectively, requiring a mechanism by which the two processes can be linked. This is accomplished by a virus-specific interaction between the two proteins (9,10,13,19).The ectodomain of paramyxovirus attachment proteins, including the NDV hemagglutinin-neuraminidase (HN), consists of a long stalk connected to a terminal globular domain (12). Whereas the HN globular domain mediates binding to sialic acid receptors, the stalk mediates the interaction with the homologous F protein (5,15,16).…”
mentioning
confidence: 99%
“…Many vaccine candidates are protective in animal models and, while stimulating antibody responses in humans, have failed to induce high levels of neutralizing antibodies and protection from virus challenge in human trials (reviewed in references 10 and 11). Although there are likely many reasons for these observations, one important issue has been a lack of clear understanding of the most effective form of the RSV antigens, particularly the F protein, for stimulating potent neutralizing antibodies.The paramyxovirus F protein is folded into a metastable conformation and upon fusion activation refolds, through a series of conformational intermediates, into the postfusion conformation, which is structurally very different from the prefusion form (12)(13)(14)(15)(16)(17)(18)(19). While it is logical to assume that the prefusion form of F protein should be more effective in stimulating optimally neutralizing antibodies, recent structural studies have shown that the postfusion form of the F protein contains at least some epitopes recognized by neutralizing monoclonal antibodies (17, 18).…”
mentioning
confidence: 99%
“…The paramyxovirus F protein is folded into a metastable conformation and upon fusion activation refolds, through a series of conformational intermediates, into the postfusion conformation, which is structurally very different from the prefusion form (12)(13)(14)(15)(16)(17)(18)(19). While it is logical to assume that the prefusion form of F protein should be more effective in stimulating optimally neutralizing antibodies, recent structural studies have shown that the postfusion form of the F protein contains at least some epitopes recognized by neutralizing monoclonal antibodies (17,18).…”
mentioning
confidence: 99%
“…The paramyxovirus HN protein stalk domain carries specificity determinants for F-protein activation, affects neuraminidase activity, and contributes significantly to the oligomerization of the protein (1,3,12). Mutational studies of the NDV HN stalk have examined effects on membrane fusion, NA activity, hemadsorption, F-protein complex formation, and oligomerization (13)(14)(15)(16).…”
mentioning
confidence: 99%